STAGES IN EVOLUTION AND BIOGEOGRAPHY OF PERMIAN AMMONOIDS - Leonova T.B. (My University, 1999)
The generic diversity of Permian ammonoids is analyzed, and four evolutionary stages of the fossils are distinguished. The diversity dynamics is elucidated for five principal distribution areas: the Paleotethyan, Uralian, American, Arctic, and Australian provinces. Certain trends of ammonoid biogeographic distribution are characterized for principal stages of their evolution.
Keywords: Permian; Paleozoic::Permian; Палеозой::Пермская